2009
DOI: 10.1002/ejic.200900699
|View full text |Cite
|
Sign up to set email alerts
|

Self‐Assembly from Two‐Dimensional Layered Networks to Tetranuclear Structures: Syntheses, Structures, and Properties of Four Copper–Thiacalix[4]arene Compounds

Abstract: Two new copper–thiacalix[4]arene compounds, [CuI2Cl2(H4TC4A)](CH3OH) (1) and [CuI2Cl2(H4PTC4A)](CH3OH)(CHCl3)0.5 (2) (where H4TC4A = p‐tert‐butylthiacalix[4]arene and H4PTC4A = p‐phenylthiacalix[4]arene), were synthesized by the solvothermal method in the mixed CH3OH/CHCl3 (1:1) solvent and reassembled in air at room temperature to two other structures, [CuII4Cl3(HCO2)(TC4A)(CH3OH)2(H2O)](CHCl3)(CH3OH)2.7 (3) and [CuII4Cl4(PTC4A)(CH3OH)4] (4), respectively. All these four compounds were characterized by TG ana… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
23
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(23 citation statements)
references
References 31 publications
0
23
0
Order By: Relevance
“…Moreover, the fragility of these frameworks precludes extensive investigations, including catalysis. Although some few reports deal on the construction of coordination compounds assembled by thioether ligands bound to the harder Cu(II) ion [59][60][61][62], we are not aware of any 3D material of this type. In light of the application of Cu(II)-containing materials in the domain of molecular magnetism [63][64][65][66], the crystal engineering of 3D materials combining the paramagnetic Cu(II) salts and organosulfur ligand appears as interesting perspective.…”
Section: Resultsmentioning
confidence: 95%
“…Moreover, the fragility of these frameworks precludes extensive investigations, including catalysis. Although some few reports deal on the construction of coordination compounds assembled by thioether ligands bound to the harder Cu(II) ion [59][60][61][62], we are not aware of any 3D material of this type. In light of the application of Cu(II)-containing materials in the domain of molecular magnetism [63][64][65][66], the crystal engineering of 3D materials combining the paramagnetic Cu(II) salts and organosulfur ligand appears as interesting perspective.…”
Section: Resultsmentioning
confidence: 95%
“…TCA (L1, cone conformation, figure 3 a), with its coordinating sulphur atoms in the ring of the macrocyle, leads to the formation of an extended networks when combined with transition metal ions, which was also observed with the parent compound where a non coordinating phenyl group has been appended at the upper rim (L2, cone conformation, figure 3 c): by mixing L1 or L2 (figure 4 a&c) together with Copper(I) chloride, two 2D compounds with the same connectivity of formula [Cu2Cl2(L1)](CH3OH) (figure 4 b) and [Cu2Cl2(L2)](CH3OH)(CHCl3)0. 5 (figure 4 d) were obtained and their luminescent and magnetic properties in the solid state were also studied [16]. The connectivity of both 2D compounds are ensured by the affinity of the Cu(I) cations towards S atom, resulting the formation of the network.…”
Section: Tcamentioning
confidence: 99%
“…Adapted from Ref. [16] The second example of Coordination Polymer arises from very simple tetrasubstituted p-Hcalix [4] Several examples of Coordination Polymers based on thiacalix [4]arene associated with alkali potassium cations with non coordinating groups were provided by Hamada et al For example when thiacalix [4]arene is combined with KH, a compound of formula structure [K (L1)](MeOH) with a 2D structure was obtained (figure 6 b), through O and S coordination of the thiacalix [4]arene to K + cations [18]. The porous properties of the compound are presented.…”
Section: Tcamentioning
confidence: 99%
“…[17] Fitting of the inverse susceptibility to the Curie-Weiss law showed that the complex had appreciable anti-ferromagnetic coupling at low temperatures. The temperature-dependent susceptibility for this complex and several Cu II calixarene complexes [17,26,27] have not been fitted with an appropriate Hamiltonian. This is perhaps (a) 3 surprising as the coordination environment of these materials is reminiscent of the environment of the Cu II atoms in oxo-bridged dicopper(II) compounds.…”
Section: Resultsmentioning
confidence: 99%